2012
DOI: 10.4028/www.scientific.net/amr.430-432.586
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Wave-Absorbing Properties of Pumice Lightweight Aggregate Concrete

Abstract: Wave-absorbing properties of ordinary concrete and pumice lightweight aggregate concrete which contained expanded perlite and carbon black were investigated in this paper. The results indicated that pumice lightweight aggregate concrete had ideal wave-absorbing properties. Within the scope of 2 ~ 18 GHz, the lowest reflectivity reached to -20 dB and better than the bandwidth of -5 dB up to 9 GHz. Meanwhile, the incorporation of proper carbon black absorber and expansion perlite can improve wave-absorbing prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Ma Jiansuo [10] and ZhangYu [12] employed "wrapped slurry" processing to seal the holes of pumice, and studied the pumice concrete's performance. Lv xingjun [14] used shell to strengthen pumice in order to improve cylinder compressive strength and reduce the water absorption of pumice. The results showed that that method significantly improved the compression strength of the pumice aggregates concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Ma Jiansuo [10] and ZhangYu [12] employed "wrapped slurry" processing to seal the holes of pumice, and studied the pumice concrete's performance. Lv xingjun [14] used shell to strengthen pumice in order to improve cylinder compressive strength and reduce the water absorption of pumice. The results showed that that method significantly improved the compression strength of the pumice aggregates concrete.…”
Section: Introductionmentioning
confidence: 99%